Strategic behaviours and priority rules in debt restructuring - Comin, Sara (European Insolvency and Restructuring Journal, 2023)
The paper analyses the correlation between the various categories of strategic behaviours that may be adopted by the parties involved in a debt restructuring and the three types of priority rules that might apply: the so called “absolute priority rule” and “relative priority rule” and a rule that can be named “no priority rule”. More specifically, the article offers an overview of the literature concerning the opportunistic behaviours in a debt restructuring and reports a lack of categorisation and agreement on the meaning of the terms used to label such behaviours, revealing how this negatively affects the discussion on priority rules. Therefore, the paper aims at filling such gap, by presenting a systematic analysis of four categories of strategic behaviour: “holdout”, “holdup”, “free-riding” and “rent-seeking”. On the basis of such categorisation, the paper proceeds with an analysis of the ways in which each category of opportunistic behaviour is affected by the application of each of the “absolute priority rule”, the “relative priority rule” and the “no priority rule”.